IDENTIFYING STUDENTS LEARNING STYLE PREFERENCES AT IAIN TERNATE - Jamulia, Jumahir (International Journal of Education, 2018)
Students are unique entities with different characteristics to be paid attention to by teachers in the teaching and learning process. Teachers can teach their students based on their unique characteristics. Students’ learning style is one of the factors which will contribute toward students’ success in learning. This paper is aimed to identify and prepare information about students’ major perceptual learning style preferences and minor learning preferences. This research was conducted at State Institute for Islamic Studies (IAIN) Ternate towards 116 students of Shariah Department of academic year 2012/2013 who were chosen purposively as the sample of the research. The data of the research were elicited by using Reid’s (1987) Perceptual Learning Style Preferences (PLSP). The data were analyzed with descriptive statistics by using Microsoft Excel 2007. The findings of the research show that the students’ major perceptual learning style preferences were visual (mean = 40.2), and the minor perceptual learning style preferences were kinesthetic (mean = 37.0), individual (mean = 36.7), tactile (mean = 36.3), auditory (mean = 35.8), and group (mean = 33.9). The characteristics of students with visual learning style preferences are: (a) The students remember better when they read instructions; (b) The students understand better when they read instructions; (c) The students learn better by reading what the teacher writes on the writing-board; (d) The students learn better by reading than by listening to someone; and (e) The students learn more by reading textbooks than by listening to lectures.